Growth of Yearling Heifers under Different Systems of Grazing on Sewan (Lasiurus Sindicus) Grassland - Kackar, N L; Bawa, A K (Annals of Arid Zone, 2016)
The study involving four grazing treatments with yearling heifers of 75-100 kg body weight and stocked at 3 ha/animal revealed the body weight gain from 55.2 kg/ heifer/year to 62.5 kg/heifer/year. Variations in the body weight within treatments were, however. statistically non-significant. Yearly variations in the body weight gain that ranged from 36.1 kg to 88.0 kg/heifer,were highly significant. Marked seasonal variations in the body weight gain were influenced by seasonal variations in the production of herbage which inter alia appeared to be related to the quantum and to the distribution pattern of rains. Maximum body weight gain, i.e., 19.4 kg was recorded during the rainy period, i.e., August to September and minimum, i.e., -2.02 kg, during dry period, i.e., April-May.